Impact of Service Quality on Customer Satisfaction and Loyalty - Shrestha, Purna Man (Management Dynamics, 2021)
This paper has analyzed the impact of service quality on customer satisfaction and customer loyalty of NTC. For this purpose, this paper has used five dimensions of service quality - tangibles, reliability, assurance, empathy and responsiveness, as proposed by Parasuraman, Berry and Zeithaml (1991). The required data for the study has been collected using a structured questionnaire from the customer of NTC of Surkhet Valley. Using the multiple regression analysis, this paper finds the significant positive impact of all the service quality dimensions on customer satisfaction and loyalty. Furthermore, "Reliability" is the strongest dimension of service quality that impacts customer satisfaction, whereas "Empathy" is the strongest dimension of service quality for impacting customer loyalty. In addition, this paper also finds "Customer Satisfaction" as the important factor for making customers loyal towards the service provided by the organization. Thus, this paper concludes that service quality is the most important factor that makes customers satisfied and loyal. The management of NTC can implement the findings of this study to develop a strategy related to customer service, which creates corporate value and leads to customer satisfaction and loyalty.